Perempuan sebagai Simbol Kesuburan: Kajian Ekofeminisme terhadap Tradisi Peminangan di Suku Wewewa Sumba Barat Daya - Konradus Doni Kelen; Kanisius Kami; Paulus Ama Kamuri; Gabriela Triola (Ideas Publishing, 2026)
This research is based on the importance of understanding the role of women as symbols of fertility in the marriage proposal tradition of the Wewewa community in Southwest Sumba Regency. The marriage proposal tradition is not only understood as a process of uniting two families but also contains cultural, social, and ecological values that place women at the center of the sustainability of life. The purpose of this research is to describe the meaning of women as symbols of fertility in the marriage proposal tradition and to analyze it through ecofeminist studies. The method used in this research is qualitative, with data collection techniques including in-depth interviews, observation, and documentation of traditional leaders and the Wewewa community. The results indicate that women in the marriage proposal tradition are viewed as sources of life, successors to descendants, and guardians of harmonious relations between humans, nature, and culture. Ecofeminist studies demonstrate the link between respect for women and respect for nature in the lives of the Wewewa community. This research is expected to provide a reflection on maintaining local cultural values while strengthening respect for women and the environment.